1994
DOI: 10.1111/j.1365-2796.1994.tb01084.x
|View full text |Cite
|
Sign up to set email alerts
|

The changes in blood pressure after acute stroke: abolishing the ‘white coat effect’ with 24‐h ambulatory monitoring

Abstract: Although there was a large fall in causal BPs seen in both groups there was only a small, but a significant fall in mean 24-h BP over the first week following hemispheric stroke that was not seen in control subjects. Although the 'white coat effect' and admission to hospital play an important part in the high casual BP observed in the days following acute stroke they are unlikely to be the sole factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
3
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 8 publications
3
44
3
1
Order By: Relevance
“…18,19 Additionally, it provides high number of readings and abolishes digit preference, allowing a more precise documentation of BP values in acute stroke. Therefore, the aim of the present study was to investigate in stroke subtypes of different aetiopathogenic mechanisms the relation of BP values during the first hours of ictus to demographic characteristics, stroke risk factors, concomitant diseases, stroke severity and acute stroke complications (brain oedema and haemorrhagic transformation), by means of 24-h BP monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Additionally, it provides high number of readings and abolishes digit preference, allowing a more precise documentation of BP values in acute stroke. Therefore, the aim of the present study was to investigate in stroke subtypes of different aetiopathogenic mechanisms the relation of BP values during the first hours of ictus to demographic characteristics, stroke risk factors, concomitant diseases, stroke severity and acute stroke complications (brain oedema and haemorrhagic transformation), by means of 24-h BP monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…1 Because cerebral autoregulation is impaired after an acute stroke, cerebral blood flow is believed to be very sensitive to changes in systemic BP. Therefore, elevation of BP after acute stroke may be of benefit in terms of increasing cerebral blood flow in the ischemic areas of brain.…”
mentioning
confidence: 99%
“…It is well known that BP levels are commonly elevated during acute stroke and fall spontaneously during subsequent days. [2][3][4] Most studies were based on casual measurements and included only a few very old patients. 2,4,19 The advantages of 24H BPM compared with casual BP values is that more measurements are yielded over time, information on BP load and variability are generated and the white coat effect and observer bias are eliminated.…”
Section: Discussionmentioning
confidence: 99%
“…There was no long-term follow-up. 3,[20][21][22][23][24][25] In the present study, we examined very old patients with acute stroke and used both admission casual BP levels and 24H BPM. Previous studies have demonstrated contradictory results regarding the effect of admission BP levels on outcomes in patients with acute stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation